Nanoplatforms for Plasmon-Induced Heating and Thermometry - Debasu, Mengistie L.
Plasmonic nanostructures concentrate light and heat within a small volume at the nanoscale, offering potential applications in nanotechnology and biomedicine (e.g., hyperthermia). However, the precise quantification of the actual temperature rise in the vicinity of such nanosystems poses considerable challenges. Here, we present a new heater-thermometer nanoplatform capable of measuring the plasmon-induced local temperature increase of Au nanorods via the ratiometric upconversion of (Gd, Yb, Er)(2)O-3 nanothermometers upon 980 nm laser excitation (up to 102.0 Wcm(-2)). The local temperature rise, 302-548 K (maximum temperature sensitivity 1.22% K-1, uncertainty 0.32K and repeatability > 99%), is assessed using Boltzmann's distribution of the Er3+ (2)H1(11/2) -> I-4(15/2)/S-4(3/2) -> I-4(15/2) intensity ratio. The nanoplatforms are biocompatible with MG-63 and A549 cells and were mapped within the former using hyperspectral imaging, opening up an avenue to monitor the cellular uptake of Ln(3+)-based nanoplatforms.